Long-Term Weight Maintenance after a 17-Week Weight Loss Intervention with or without a One-Year Maintenance Program: A Randomized Controlled Trial - Tuula Pekkarinen; Jarmo Kaukua; Pertti Mustajoki (Journal of Obesity)
Background. Weight lost by obese patients is almost always regained over time. Extended treatment may improve maintenance, but solid evidence is lacking. Purpose. We determined effectiveness of maintenance therapy after a weight loss program. Methods. Together 201 patients (mean age 47 years and BMI 42 kg/m2, 71% women) were randomly assigned to either a 17-week weight loss program followed by a one-year maintenance program or to a weight loss program without subsequent maintenance intervention. The weight loss program included behavior modification and a very-low-calorie diet, and maintenance program behavior modification. The primary outcome measure was percentage of patients with 5% or more weight loss at the end of maintenance (week 69) and one year later (week 121). Secondary outcomes were weight related changes in lifestyle and quality of life. Results. At week 69, 52% of the patients with and 44% of those without maintenance program had lost weight ≥5%, P=0.40, and, at week 121, 33% and 34%, P=0.77, respectively. At week 121 secondary outcomes did not differ between the groups among those successfully followed up. Conclusions. This one-year maintenance program was not effective in preventing weight regain in severely obese patients. Trial Registration. This trial is registered under clinicaltrials.gov Identifier: NCT00590655.